Peningkatan Kemampuan Berpikir Kritis Siswa Melalui Model Pembelajaran Kooperatif Tipe Jigsaw dengan Media Game Monopoli - Diyanah, Ishmatud; Atok, A. Rosyid Al (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to describe the application and analysis of student's critical thinking skills in learning that used a jigsaw cooperative model with monopoly game media. The study used classroom action research with a quantitative descriptive approach. The application of the jigsaw type cooperative learning model with monopoly game media was applied in several stages, namely group formation, rolling dice in turns, followed by transaction activities in the form of a combination of answering questions, renting, selling, and buying assets until finally one of the students became an absolute rich person called a monopolist. The student's critical thinking ability before taking action measured through the pretest. It showed that the percentage of completeness obtained by students was 65.6 percent with a minimum completeness criterion of 75. The student's critical thinking ability after the action in cycle I showed that there was a change in the percentage of completeness obtained by students of 66.67 percent of the pretest results to 76.67 percent of the post-test results. In the second cycle, there was a change of 76.67 percent from the pretest results to 90 percent from the post-test results, thus student's critical thinking skills in learning that used a jigsaw cooperative model with monopoly game media increased by 10 percent in cycles I and 13.33 percent in cycle II.